1976
DOI: 10.1104/pp.58.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Alteration of Plant Plasma Membranes Induced by Auxin and Calcium Ions

Abstract: Ultrastructural changes in isolated and in situ plasma membranes of etiolated soybean hypocotyls (Glycine max L. cv. Wayne) were induced by indole-3-acetic acid (IAA), other auxins, and calcium chloride. Fixed and embedded preparations were stained by a phosphotungstate-chromate procedure to identify and accentuate plasma membrane. Measurements were on micrographs obtained with an electron optical system calibrated and corrected for reproducible and accurate size measurements. Plasma membranes treated for 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Only one recent study (1) reports IAA-induced hyperpolarization (-20 mV) using two concentrations (1 and 1 00 M), and it was suggested that the response was concentration independent. In contrast we show here that the NAA-induced Em changes were described by a bell-shaped curve as a function of auxin concentration similar to that described for IAA effects on membrane thickness (22) and calcium binding properties (3) of soybean membranes.…”
mentioning
confidence: 44%
See 1 more Smart Citation
“…Only one recent study (1) reports IAA-induced hyperpolarization (-20 mV) using two concentrations (1 and 1 00 M), and it was suggested that the response was concentration independent. In contrast we show here that the NAA-induced Em changes were described by a bell-shaped curve as a function of auxin concentration similar to that described for IAA effects on membrane thickness (22) and calcium binding properties (3) of soybean membranes.…”
mentioning
confidence: 44%
“…Ultrastructural alterations were induced by auxin in isolated and in situ soybean plasma membranes (22). Modifications of the physical properties of membranes after auxin treatment have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These results are suggestive of better preserved membranes which may contribute to the delay in senescence observed in rin mutant. Ca has been reported to maintain the integrity of membranes (6,8,13,14) and delay senescence (14,25). The mutant failed to show any increase in membrane permeability during fruit development and maturation (18) which normally occurs during ripening (2,22) of fruits.…”
mentioning
confidence: 99%
“…Divalent cations contribute to membrane stability by altering the structure of the membrane (13,24). For example, Jones and Lunt (8) in their review pointed out that electron microscope studies have shown extensive disintegration of mitochondria, ER, and cytoplasmic membranes in various Ca-deficient plants.…”
mentioning
confidence: 99%
“…One potential explanation of this observation is that most of the binding sites are saturated at I jig/ml. Second, transport was not affected by 2,6-D at or below 10 ,ug/ml and 4-D was less inhibitory than 2,4-D at 10 ,ug/ml and was not inhibitory at 1 jg/ml. All three compounds were inhibitory at 50 ,ug/ml.…”
Section: Resultsmentioning
confidence: 99%